O mecanismo de transmissão de preços do petróleo para a gasolina e para o diesel nos EUA nos anos 2000 - Pieri, Lorenzo (2013)
Through an Error Correction Model this study explores possible asymmetries in the passthrough of the oil prices to gasoline and diesel prices in the US market and, mainly, analyzes if the trends reversals of those refined oil products demand at the above market affected the price transmission mechanism. Using monthly date from January 2001 to December 2012, the results for gasoline indicated that there was evidence of passthrough due to the demand shift. However, it is worth noting that this result occurred concurrently with the period of recovery in prices witnessed after the 2008 crisis. Regarding diesel, there is no evidence that there were changes in the passthrough. Finally, we found evidence of the WTI decline as an oil reference due to its devaluation from 2010.